The Influence of Contextual Teaching and Learning Methods and Learning Motivation on Students' Negotiation Text Writing Skills - Dela Syafira; Afnita Afnita (STAI Hubbulwathan Duri, 2022)
The purpose of this study is to analyze how students' negotiating text writing abilities are affected by contextual teaching and learning (CTL) strategies and learning motivation. This kind of study uses a quantitative experimental design. This approach to research is essentially an experiment. 159 participants made up the study's population. 32 people were sampled using the purposive sampling technique in class X AKT, the experimental class, and 31 in class X RPL, the control class. Utilizing questionnaires to gauge students' motivation for learning and performance exams to gauge their proficiency with negotiating text-writing. According to the results of the research, students in class X are motivated to learn using the contextual teaching and learning (CTL) technique. The following can be said about the influence. First off, pupils who used the contextual teaching and learning (CTL) technique performed higher on tests of their negotiating text writing abilities than those who used the traditional approach. Second, students who use the contextual teaching and learning (CTL) technique and have high learning motivation have better negotiating text writing skills than students who use traditional methods and have high learning motivation. Third, students who use the contextual teaching and learning (CTL) technique and have low learning motivation have better negotiating text writing skills than students who use traditional methods and have low learning motivation. Fourth, the contextual teaching and learning (CTL) method model interacts with learning motivation to influence students.